Efficience of Republic of Moldova stone fruit species restructuration within the condition of globalisation - Vasile Mladinoi; Maria Pîntea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
In the article there are presented data regarding contribution of continuous development of stone fruit trees assortment for the republic of Moldova. As a result of comparative analysis evaluated researches and practical actions there are stands out enlargement of total surface of established orchards of stone crops by 45 thousand ha. Creation and implementation of new stone varieties there are directed to local and foreign modern fruit markets, especially for fresh consumption, obtained annual quantity has increased by more than 109 thousand tons.
Keywords: 330; stone fruit trees species; local and introduced varieties; adaptability; efficiency; Republic of Moldova